Aynura, Khudiyeva - (:unkn) unknown (My University, 2026)
Aynura Khudiyeva Ilyas received her Bachelor's degree (2007) and Master's degree (2010) in Mathematics, both with honors, from the Faculty of Mechanics and Mathematics of Baku State University. Owing to her outstanding academic performance, she began her teaching career in 2007 as a mathematics teacher at the Heydar Aliyev Modern Education Complex. In 2012, she was admitted to the part-time doctoral program at the Institute of Mathematics and Mechanics of the Azerbaijan National Academy of Sciences, specializing in 2003.01 – Mechanics of Fluids, Gases, and Plasma. She also worked as a Junior Researcher in the Department of Fluid and Gas Mechanics. Under the supervision of Professor Faiq Nagiyev, she completed her doctoral dissertation entitled "Wave Propagation in a Stratified Fluid Taking Capillary Effects into Account." In 2017, she was awarded the degree of Doctor of Philosophy (PhD) in Mathematics. Dr. Khudiyeva is the author of 15 scientific publications, including journal articles and conference papers published in national and international academic journals. Five of her publications are indexed in Scopus, and one has been published in a high-impact journal indexed in the Web of Science Core Collection (Clarivate Analytics). She is also the author of four educational manuals. She has actively presented her research at scientific seminars and international conferences, where her work has received professional recognition. Her contributions to mathematics and fluid mechanics have been acknowledged through several international certificates and awards. Her research interests include fluid mechanics, gas dynamics, wave propagation, capillary phenomena, and applied mathematics. Alongside her research activities, she is actively engaged in teaching and contributes to the academic and educational development of university students.